PENATALAKSANAAN EDUKASI PERSONAL HYGIENE UNTUK MENINGKATKAN PENGETAHUAN IBU HAMIL - Erna Kasim; Nurkamiden, Ayu; Magdalena Limbong; Ekayanti Ahmad; Andi Tenriola Fitri (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2024)
Knowledgepersonal hygiene in pregnant women is very important because good knowledge can improve health in pregnant women themselves. Research purposes:. This study aims to identify the management of education aboutpersonal hygiene in pregnant women. Method: In this study the methods used were interviews and observation. Results:After conducting a case study between Mrs